Pendekatan Humanistik dalam Konseling Kelompok untuk Mengatasi Kesepian pada Gen Z (Dewasa Awal) - Vonda Nabila Anindra; Sofyan Abdi; Afra Hasna; Najwa Raras Pranoto; Hermawati Artameyvia; Najwa Azzahra; Mirantri Zuraidah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study aims to explore the subjective experience of loneliness in early adult Gen Z college students through group counseling with a humanistic approach. Using a qualitative phenomenological method, six female participants aged 20–22 years participated in four group counseling sessions. Data collection was conducted through an initial questionnaire to identify participants' levels of loneliness, followed by in-depth interviews after the counseling session to explore the meaning of their experiences more comprehensively. The results showed that loneliness was associated with a lack of emotional connection, unsupportive family relationships, and shallow social interactions through social media. Group counseling proved to be a safe space to share emotions and build self-awareness, helping participants manage loneliness more healthily.